Test-retest reliability of selected HBSC items measuring problem behaviour among Slovak and Czech adolescents - Holubčíková, Jana; Kudláček, Michal; Širůček, Jan; Madarasová Gecková, Andrea (Central European journal of public health, 2018)
OBJECTIVES: The purpose of this study was to assess the test-retest reliability of selected items based on self-reports, measuring problem behaviour in the Slovak and Czech version of the HBSC survey questionnaire. METHODS: The data from test-retest study, based on an international Health Behaviour in School-aged Children (HBSC) study and consistent with its methodology, were analysed. A sample of 580 primary school pupils (51.2% of boys), grades five and nine participated in a test and retest with a four-week interval. Six items concerning problem behaviour were evaluated overall and stratified by gender and age. RESULTS: Analyses of test-retest reliability indicated modest (0.30 to 0.49), moderate (0.50 to 0.69), or high (0.70 to 1.00) reliability across nearly all questions, with some reliability differences in analyses by gender and age. In general, findings of present study suggest the moderate reliability of measures of smoking, drunkenness, fighting and negative relationship to school, modest reliability of measures of bullying behaviour, and low reliability of measure of truancy. CONCLUSIONS: The overall findings of this study suggest that most of selected indicators in the HBSC survey questionnaire have satisfactory test-retest reliability. Further test-retest studies in a large and diverse sample, as well as validity studies, should be considered for the future HBSC study.
Keywords: Adolescent Behavior; Male; zpráva o sobě; Slovakia; Slovenská republika; problem behaviour; Adolescent; Problem Behavior; Česká republika; mužské pohlaví; reprodukovatelnost výsledků; průzkumy a dotazníky; Reproducibility of Results; mladiství; Czech Republic; lidé; ženské pohlaví; Humans; adolescence; Self Report; problémové chování; test-retest reliability; Female; Surveys and Questionnaires; chování mladistvých